Street Furniture Design Consultation Signage for Place’s Name for Puri Kembangan Fly Over Area - Ramadhan, Ali; Anggita, Dena; Muladi, Edy (International Journal of Community Service Learning, 2020)
A flyover is known as a facility on the road as an option to drive to reach the destination. On the streets, signage is known as a medium to explain the direction or purpose of someone to be able to know the direction and purpose. As street furniture, signage is one of the facilities that are not infrequently present somewhere. So someone can find out where he is. By using the consultation method and including interviews with partners, solving the problem through community service programs will be carried out in the form of signage design that will be made on any part that requires information about the place or crossroads in the basement area of the flyover in the area of West Jakarta. The signage design of the consultation results as a guide can be continued to the stage of making the object by taking into account the elements of the environment and the people in the area. So that in its application, signage design can help the general public to know the direction and the area to be addressed.